A Blockchain-Based Privacy Preservation Scheme in Mobile Medical. (22nd March 2022) - Wen, Haiying; Wei, Meiyan; Du, Danlei; Yin, Xiangdong
Abstract : With the rapid development of mobile medical, how to establish an effective security mechanism to protect data security and privacy while users enjoy medical services has become an urgent problem to be solved. Aiming at the easy leakage of privacy in mobile medical terminals and untrustworthy data, we make use of a role-separated mechanism to generate trusted anonymous certificates. We propose a lightweight identity authentication scheme and adopt blockchain to protect the security of medical data. Meanwhile, in view of the problems of transparency and visibility of blockchain information, we adapt the searchable encryption algorithm to realize ciphertext processing in the whole life cycle. Experiments show that our scheme can reduce the cost of computation on the basis of ensuring traffic. In the process of dynamic updating of ciphertext keywords, except the keyword identifier, less information is leaked to the server, which protects privacy of users.